Thyroid profile as a marker of poor prognostic factor in patients with acute coronary syndrome: a tertiary care hospital based observational study - Paudel, Navaraj; Alurkar, Vijay Madhav; Kafle, Ramchandra; Maskey, Abhishek; Sapkota, Subash (Nepalese Heart Journal, 2018)
Background and aims: Serum thyroid hormonal changes can occur in acute or chronic non-thyroidal systemic illness including acute coronary syndrome in otherwise euthyroid individuals. In this study we aimed to assess thyroid hormonal profile in patients presenting with acute coronary syndromes (ACS) and compare between ST segment elevated myocardial infarction and unstable angina/Non ST segment elevated myocardial infarction. Methods: A hospital based, retrospective, observational comparative study was designed. Data of all patients with acute coronary syndrome presenting to hospital were collected from July 2015 through June 2017 in a pre-structured proforma and analyzed. Results: A total of 200 ACS patients between 23 years to 88 years with mean age of 61.33 ± 12.30 years were studied. One hundred and twenty seven (63.5%) were males. Among them 116 (58%) was ST segment elevated myocardial infarction (STEMI) patients while 84 (42%) were unstable angina/ non-ST elevated myocardial infarction (UA/ NSTEMI) patients. Total 47 (23.5%) patients had abnormal TFT of which 28(59.5%) had Euthyroid Sick Syndrome, 12(25.5%) had subclinical hypothyroidism, 5(10.6%) had subclinical hyperthyroidism and 2(4.25%) had low fT4 with normal fT3 and normal TSH. There was significant difference in TFT in patients with STEMI and UA/NSTEMI (P=0.006).There were higher rates of heart failure (p= 0.001 & 0.003 in STEMI & UA/NSTEMI respectively), longer length of hospital stay (3+0.17 days) and high mortality (more than 4 fold) in all types of ACS patients with abnormal TFT than ACS patients with normal TFT. Conclusion: There is higher prevalence of abnormal thyroid hormonal findings in ACS causing significant morbidity and mortality.